Russia's wartime investment boom - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
A sharp increase in fixed investment has been a key factor supporting Russia's economy in recent years. This brief highlights the drivers of Russia's recent investment boom. During 2022, the first year of the full-blown war in Ukraine, investment growth was dominated by increased budget spending, war-related investment in construction of transport and warehouse infrastructure, as well as investment in oil & gas production in western Siberia. In 2023, the emphasis in investment growth shifted to firms funding investment out of pocket and manufacturing, particularly firms involved in war-related or resource-intensive branches. Although intellectual property (IP) only represents a small share of Russia's total investment, IP investment has increased sharply in recent years.
urn:nbn:fi-fe2024051530876
Keywords: 330; Russia; war; economy; investment